Nomes gerais e outras formas de indeterminação do sujeito: um estudo variacionista sobre o português brasileiro (PB) de Bambuí e sobre o português europeu (PE) de Coimbra - Fernanda Carla de Oliveira (2022)
Subject indetermination, in a variationist framework, has already been studied by authors such as Milanez (1982), Menon (1994), Setti (1997), Godoy (1999), Carvalho (2010), Souza (2014), Barbosa (2016) among others. All of them demonstrated that the forms provided by traditional grammars are not the only ones that serve as a source of indetermination in Portuguese. Thus, this study seeks to draw a comparison between Brazilian Portuguese (BP) and European Portuguese (EP) to observe the relevance of general nouns in the set of indeterminate variants, verifying the influence of linguistic and extralinguistic factors in the realization of the phenomenon. It should be noted that general nouns are defined by Halliday and Hasan (1995 [1976]) as a borderline case between a lexical item and a grammatical item, as they contain minimal semantic features, and they were selected for this study because some studies, such as those by Oliveira (2018) and Amaral and Oliveira (2019), show that these items are able to indeterminate. The analyzed data belong to 48 sociolinguistic recordings collected in Brazil, in Bambuí city, located in the center-west of the state of Minas Gerais, and in Coimbra city, located in central region of Portugal, in the Beira Litoral province. The general nouns found in the corpus are pessoa, pessoal, pessoas, cara, homem, povo, fulano, gente and ser humano. The other forms studied refer to those that have already been discussed in previous researches, that is, a gente, você/ocê/cê, nós/nóis, eles/ês, a verb in third-person singular form without an explicit subject (Ø+V3PS), ês, a verb in third-person plural form without an explicit subject (Ø+V3PP), a verb in infinitive form without an explicit subject (Ø+VINF), and se. The extralinguistic factors analyzed are sex and age group, and the linguistic factors tested are presence or absence of locative, presence or absence of anaphora, degree of indetermination, and more or less collective. The program used for data analysis is GoldVarb X. It seems that BP and EP demonstrate different panoramas regarding the indetermination resources used by the speakers, because, while the informants from Bambuí choose ways such as a gente and você/ocê /cê, preferably, to indeterminate the subject, the informants from Coimbra use, preferably, the form nós and the indetermination forms foreseen by the grammars, that is, a verb in the third-person plural without an explicit subject (Ø+V3PP) and se. As far as general nouns are concerned, they are used with similar frequency by Brazilian and Portuguese informants. In Bambuí, the factors sex, presence or absence of anaphora, and degree of indetermination favor indetermination through general nouns. In Coimbra, the presence or absence of locative, age group, degree of indetermination, and more or less collective were selected as statistically relevant. It is concluded that informants from BP and EP use general nouns; however, the distribution of these forms within the set of these nouns occurs differently in the two. Furthermore, the linguistic and extralinguistic factors which influence this variant are also different in the two locations. It is also observed that the subject's indeterminacy, analyzed through degrees (total or partial), can solve the confusion between the indefiniteness and indetermination of the term. In summary, this research demonstrates how the general nouns are relevant in the set of these variants and how the comparison between two cities in different countries brings significant results for research in the area.